Demographic factors, partial social belonging and psychological resources associated with coping - Eshel, Yohanan; Kimhi, Shaul; Marciano, Hadas; Adini, Bruria (Frontiers in Psychology, 2023)
Introduction The present study investigates the role of perceived partial social belonging (PPSB) in determining societal and individual resilience and positive and negative coping indicators. It is assumed that most people aspire to belong and be integrated into their society. A sense of only partial belonging is therefore distressing for them. Methods Two hypotheses are examined in the current study: (a) A higher level of PPSB will predict a lower level of resilience and a higher level of psychological symptoms. (b) PPSB will mediate the associations between three stress-evoking demographic characteristics (younger age, low income, and gender) and the lower psychological resilience and higher distress associated with these demographic characteristics. These hypotheses were examined using a sample of the Israeli Jewish public (N = 1,502) who responded to an anonymous questionnaire about the investigated issues. The data were collected by an internet panel company possessing a database of more than 65,000 residents, representing the varied components of the Israeli society. Results The findings supported our hypotheses: (a) PPSB negatively predicted societal and individual resilience and hope and positively predicted distress symptoms and sense of danger. (b) PPSB mediated the effects of the investigated demographic variables on these psychological variables. Conclusion These results are discussed in association with the concept of belonging competencies. Our findings display that being unsure about one’s belonging to a desired social group, has a major role in increasing psychological distress and sense of danger and in reducing hope and both individual and societal resilience.